Desain Kemasan Ilustratif untuk Meningkatkan Nilai Pasar Permainan Tradisional - Kristiana, Nova; Patria, Asidigisianti Surya; Martadi; Anggalih, Nanda Nini; Laksmi, Arieviana Ayu (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
Kampoeng Dolanan Surabaya is one of the communities that actively introduces traditional Indonesian games. In this Community Service program, the team will help increase the selling value of traditional toys through packaging design innovations in Kampoeng Dolanan, a community that preserves traditional games in Surabaya. The focus of this activity was the Sociopreneur division, Dolipstore, which faced challenges in attracting the attention of the audience due to the unattractive packaging of the product. Through a series of stages, namely feasibility studies, coordination, design, and partner assistance, an illustrative packaging design for traditional toys such as boats, bekel balls, marbles, tops, and yoyos was produced. The results include an increase in the visual appeal of the product, the expansion of marketing to the mall. This program not only has a positive impact on improving the partners' economies, but also supports the preservation of local culture. In conclusion, illustrative packaging design is an effective solution in increasing the market value and competitiveness of traditional toy products.